Analisis Strategi Pemasaran Digital Travel Arnes Menggunakan Model AISAS melalui Instagram, Tiktok, Facebook, dan Website dalam Meningkatkan Daya Tarik Konsumen - Didan Abdilah; Aris Rinaldi (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the digital marketing strategy implemented by Travel Arnes using the AISAS model through Instagram, TikTok, Facebook, and its website to increase consumer attractiveness. A descriptive qualitative approach was employed with purposive sampling, involving management representatives and consumers who had interacted with Travel Arnes’s digital content. Data were collected through observation, in-depth interviews, and documentation. The findings show that consumer attractiveness is influenced by all AISAS stages: attention through engaging visual content, interest through promotional information, search through social media and website access, action through travel service purchases, and share through consumer testimonials and online experiences. The study concludes that implementing the AISAS-based digital marketing strategy across multiple digital platforms positively contributes to increasing consumer attractiveness. However, improvements in content consistency, digital innovation, and the use of interactive features are recommended to strengthen the company’s competitiveness in the digital era.